Reducing climate impacts of beef production: A synthesis of life cycle assessments across management systems and global regions. (3rd March 2021) - Cusack, Daniela F.; Kazanski, Clare E.; Hedgpeth, Alexandra; Chow, Kenyon; Cordeiro, Amanda L.; Karpman, Jason; Ryals, Rebecca
Abstract: The global demand for beef is rapidly increasing (FAO, 2019), raising concern about climate change impacts (Clark et al., 2020; Leip et al., 2015; Springmann et al., 2018). Beef and dairy contribute over 70% of livestock greenhouse gas emissions (GHG), which collectively contribute ~6.3 Gt CO2 ‐eq/year (Gerber et al., 2013; Herrero et al., 2016) and account for 14%–18% of human GHG emissions (Friedlingstein et al., 2019; Gerber et al., 2013). The utility of beef GHG mitigation strategies, such as land‐based carbon (C) sequestration and increased production efficiency, are actively debated (Garnett et al., 2017). We compiled 292 local comparisons of "improved" versus "conventional" beef production systems across global regions, assessing net GHG emission data from Life Cycle Assessment (LCA) studies. Our results indicate that net beef GHG emissions could be reduced substantially via changes in management. Overall, a 46 % reduction in net GHG emissions per unit of beef was achieved at sites using carbon (C) sequestration management strategies on grazed lands, and an 8% reduction in net GHGs was achieved at sites using growth efficiency strategies. However, net‐zero emissions were only achieved in 2% of studies. Among regions, studies from Brazil had the greatest improvement, with management strategies for C sequestration and efficiency reducing beef GHG emissions by 57%. In the United States, C sequestration strategies reduced beef GHG emissions by over 100% (net‐zero emissions) in a few grazing systems, whereas efficiency strategies were not successful at reducing GHGs, possibly because of high baseline efficiency in the region. This meta‐analysis offers insight into pathways to substantially reduce beef production's global GHG emissions. Nonetheless, even if these improved land‐based and efficiency management strategies could be fully applied globally, the trajectory of growth in beef demand will likely more than offset GHG emissions reductions and lead to further warming unless there is also reduced beef consumption. Abstract : Global demand for beef is rapidly increasing, raising concern about climate change impacts. We compiled 292 local comparisons of "improved" versus "conventional" beef production systems across global regions, assessing net greenhouse gas (GHG) emission data from Life Cycle Assessments (LCA). Overall, strategies for carbon (C) sequestration on grazed lands reduced net beef GHG emissions by 62%, and growth efficiency strategies reduced net GHG emissions by 30%. Despite these improvements, net‐zero emissions were achieved only in 2% of studies. Brazilian studies had the greatest reductions in beef GHG emissions. This meta‐analysis offers insight into management strategies to reduce beef GHG emissions across global regions.